Green Brand Perceived Value: A Driver for Attitude toward Green Brand Extension - SIMAMORA, Elisabeth Rotua; INDRIANI, Farida; SETIAWAN, Budi (Journal of Environmental Management and Tourism; Vol 12 No 7 (2021): JEMT Volume XII, Issue 7(55), Winter 2021DO - 10.14505/jemt.12.7(55).16, 2021)
The purpose of this study is to develop a conceptual model that describes the process of how self-brand congruity affects attitudes toward green brand Extention. The integrated model focuses on the green brand perceived value that encourages attitude toward green brand Extention. Green brand perceived value furthermore applied to explain how green purchase intention and green trust influence attitudes toward green brand Extention. Green brand perceived value and green purchase intention have not significantly increase attitude toward green brand extension. Green brand perceived value through green brand trust directly affects and positively impacts attitude toward green brand extension.